VALU 2004 - SVT exit poll survey European parliament election 2004 - Holmberg, Sören; Hernborn, Hans; Näsman, Per (Sveriges Television, 2014)
This exit poll survey was carried out in connection with the election to the European parliament on June 13, 2004.

In VALU - Swedish exit poll surveys - voters leaving polling stations are asked by public service broadcaster Sveriges Television (SVT) to fill in a questionnaire and put it anonymously in a sealed box. After collecting and processing the responses, Sveriges Television is able to present an election forecast and an analysis of the reasons underlying the outcome of the election in it´s Election Night broadcast. The surveys are referred to as VALU, an abbreviation for vallokalsundersökning, Swedish for exit poll survey. The first exit poll survey in Sweden was carried out at the parliamentary election in 1991. Since then similar studies have been carried out in connection with all Parliamentary elections, referendums and elections to the European Parliament.

Voters leaving the polling stations were asked to fill in a questionnaire including questions on: party voted for; vote on individual or party; time for decision how to vote; party voted for if a general election was held the same day; alternative voted for in the EMU-referendum 2003; opinion on a referendum on the new EU constitution; vote in a referendum on the constitution; opinion on the Swedish EU-membership; opinion on a European federal state; confidence in Swedish politicians; placement on a political left-right scale; gender, age, occupational group and union membership. The respondents also had to indicate the importance of the policy in EU-questions, achievements in Swedish politics, old party loyalties, and the candidates, when deciding how to vote. They also had to state the importance of following issues: environment, economy, employment, agricultural subsidies in the EU, peace in Europe, national independence, change of currency to euro, refugees/immigration, enlargement of the EU, terms of enterprise, equality between men and women, defence, democracy within the EU and social welfare. Furthermore they had to state how satisfied they were with the way democracy works in Sweden and within the European Union.

Purpose:

Provide analytical support for the election night broadcast on Swedish television during the election night, and for other post-election analysis.

Denna vallokalsundersökning genomfördes i anslutning till Europaparlamentsvalet den 13 juni 2009.

Vallokalsundersökningar (exit polls) innebär att man frågar ett urval av väljare då de lämnar vallokalen dels vilket parti de röstat på och dels ett antal valsociologiska frågor. Undersökningsmetoden har med framgång använts i ett flertal länder för prognos- och analysändamål. Den första vallokalsundersökningen i Sverige genomfördes vid riksdagsvalet 1991. Liknande undersökningar har sedan dess genomförts i samband med samtliga riksdagsval, folkomröstningar och val till Europaparlamentet.

Syfte:

Ge ett analysunderlag för den valvaka som sändes i Sveriges Television under valkvällen, samt för andra eftervalsanalyser.
VALU 2004 - SVT:s vallokalsundersökning Europaparlamentsvalet 2004
VALU04
Keywords: elections; val; population migration; migration; exit polls; vallokalsundersökningar; voting; röstning; european union; europeiska unionen; european integration; europeisk integration; voting behaviour; väljarbeteende; election data; valdata; european parliament; europaparlamentet; electors; väljare; political parties; politiska partier; electoral issues; valfrågor; european parliament elections; europaparlamentsval; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap